Disadvantageous Deck Selection in the Iowa Gambling Task: The Effect of Cognitive Load - Hawthorne, Melissa J. (Eur J Psychol, 2015)
Research has shown that cognitive load affects overall Iowa Gambling Task (IGT) performance, but it is unknown whether such load impacts the selection of the individual decks that correspond to gains or losses. Here, participants performed the IGT either in a full attention condition or while engaged in a number monitoring task to divide attention. Results showed that the full attention group was more aware of the magnitude of gains or losses for each draw (i.e., payoff awareness) than was the divided attention group. However, the divided attention group was more sensitive to the frequency of the losses (i.e., frequency awareness), as evidenced by their increased preference for Deck B, which is the large but infrequent loss deck. An analysis across blocks showed that the number monitoring group was consistently more aware of loss frequency, whereas the full attention group shifted between awareness of loss frequency and awareness of payoff amount. Furthermore, the full attention group was better able to weigh loss frequency and payoff amount when making deck selections. These findings support the notion that diminished cognitive resources may result in greater selection of Deck B, otherwise known as the prominent Deck B phenomenon.